A Concise History of United States Resale Price Maintenance Arrangements and its Current Status under State and Federal Laws - GRECO, Anthony J. (Journal of Advanced Research in Law and Economics; Vol 11 No 1 (2020): JARLE Volume XI Issue 1(47) Spring 2020, 2020)
Resale price maintenance (RPM), a form of vertical price fixing is the practice whereby manufacturers of brand-name or trademark goods stipulate and attempt to enforce minimum, maximum, or actual wholesale and retail prices of such goods as they progress through the distribution chain to the final consumers of said products.